2008
DOI: 10.1002/bem.20402
|View full text |Cite
|
Sign up to set email alerts
|

No effect of mobile phone‐like RF exposure on patients with atopic dermatitis

Abstract: This study investigates the effect of exposure to a mobile phone-like radiofrequency (RF) electromagnetic field on people with atopic dermatitis (AD). Fifteen subjects with AD were recruited and matched with 15 controls without AD. The subjects were exposed for 30 min to an RF field at 1 W/kg via an indoor base station antenna attached to a 900 MHz GSM mobile phone. Blood samples for ELISA analysis of the concentration of substance P (SP), tumor necrosis factor receptor 1 (TNF R1), and brain derived neurotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The result of the present study is similar to previous studies by other researchers, De Iuliis et al (2009) and also Johansson et al (2008). The researchers have examined different absorption doses and exposure times, and had an emphasis on the major influence of absorption dose and time on the outcome.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the present study is similar to previous studies by other researchers, De Iuliis et al (2009) and also Johansson et al (2008). The researchers have examined different absorption doses and exposure times, and had an emphasis on the major influence of absorption dose and time on the outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The researchers have examined different absorption doses and exposure times, and had an emphasis on the major influence of absorption dose and time on the outcome. In collection, they concluded that, lower absorption rate and lower exposure time are not associated with any tangible results (De Iuliis et al, 2009, Johansson et al, 2008). Other scientists have noticed the effect of different types of living systems that were exposed to radiation, to explain the controversies of the findings obtained from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Johansson et al on people with atopic dermatitis (Johansson et al, 2008) reported no effect of exposure to a mobile phone-like RF in terms of the number of peaks per minute for the EDA.…”
Section: Discussionmentioning
confidence: 96%
“…Johansson et al . after a shorter (30 mn) acute exposure to mobile phone‐like radiofrequency (RF) did not found change in the levels of substance P, TNF R1 and brain neutrophic factor in sera of 15 patients with atopic dermatitis. In our experiments, reconstructed epidermis was exposed a longer period (6 h) to EMR, which may explain why we could observe change in differentiation markers.…”
Section: Discussionmentioning
confidence: 95%
“…Kimata [27][28][29] has reported that acute exposure to microwave from mobile phones (1 h) enhances allergic skin wheal responses in patients with atopic eczema/dermatitis syndrome by increasing allergen specific IgE, substance P and vasoactive intestinal peptide production. Johansson et al [30] after a shorter (30 mn) acute exposure to mobile phone-like radiofrequency (RF) did not found change in the levels of substance P, TNF R1 and brain neutrophic factor in sera of 15 patients with atopic dermatitis. In our experiments, reconstructed epidermis was exposed a longer period (6 h) to EMR, which may explain why we could observe change in differentiation markers.…”
Section: Discussionmentioning
confidence: 96%